Levels of Cognitive Complexity and the Design of Accounting Curriculum. - Caplan, Edwin H.; Amernic, Joel H.; Enns, Robin J. (The Accounting Review, 1979)
Abstract ABSTRACT: In this paper the cognitive complexity construct, which has recently been introduced into the accounting literature, is examined from the point of view of accounting pedagogy. Empirical and theoretical literature (from the discipline of education) on students' cognitive complexity, is brought to bear on the problems of teaching accounting. Given certain reasonable goals of accounting education, the analysis leads to the conclusion that knowledge about the existence of the cognitive complexity construct, and its level, is important to accounting educators from the viewpoint of curriculum design. The paper concludes by suggesting several specific implications of the construct for accounting education.